The influence of angstrom-scale roughness on the laser-induced damage threshold of single-crystal ZnGeP2 - Yudin, Nikolay A.; Khudoley, Andrei; Zinoviev, Mikhail M.; Podzyvalov, Sergey N.; Slyunko, Elena S.; Zhuravleva, Elena V.; Kulesh, Maksim M.; Gorodkin, Gennadij; Kumeysha, Pavel; Antipov, Oleg L. (Crystals)
Magnetorheological processing was applied to polish the working surfaces of single-crystal ZnGeP2, in which a non-aqueous liquid with the magnetic particles of carbonyl iron with the addition of nanodiamonds was used. Samples of a single-crystal ZnGeP2 with an Angstrom level of surface roughness were received. The use of magnetorheological polish allowed the more accurate characterization of the possible structural defects that emerged on the surface of a single crystal and had a size of ~0.5-1.5 mu m. The laser-induced damage threshold (LIDT) value at the indicated orders of magnitude of the surface roughness parameters was determined not by the quality of polishing, but by the number of point depressions caused by the physical limitations of the structural configuration of the crystal volume. These results are in good agreement with the assumption made about a significant effect of the concentration of dislocations in a ZnGeP2 crystal on LIDT.